Circular RNA of the human sphingomyelin synthase 1 gene: Multiple splice variants, evolutionary conservatism and expression in different tissues - Filippenkov, Ivan B (RNA Biol, 2015)
The human sphingomyelin synthase 1 gene (SGMS1) encodes an essential enzyme that is involved in the synthesis of sphingomyelin and diacylglycerol from phosphatidylcholine and ceramide. Among the products of SGMS1, we found new transcripts, circular RNAs (circRNAs), that contain sequences of the gene's 5′ untranslated region (5′UTR). Some of them include the gene's coding region and fragments of introns. An analysis of the abundance of circRNAs in human tissues showed that the largest transcripts were predominantly found in different parts of the brain. circRNAs of rat and mouse sphingomyelin synthase 1 orthologous genes were detected and are highly similar to the human SGMS1 gene transcripts. A quantitative analysis of the abundance of such transcripts also revealed their elevated amount in the brain. A computational analysis of sequences of human circRNAs showed their high potential of binding microRNAs (miRNAs), including the miRNAs that form complexes with Ago proteins and the mRNA of SGMS1. We assume that the circRNAs identified here participate in the regulation of the function of the SGMS1 gene in the brain.